The Role of the Embun Pelangi Batam Foundation in Assistance to Victims of the Crime of Human Trafficking (TTPO) - Alfian Eka Saputra; Ririn Hersa Yulianda; Nur Sahadatul Alawiyah; Syarifah Nia Ramadani; Afrina Caroline; Gerry Satria Osananda; Taufiqqurrachman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research analyzes the role of Yayasan Embun Pelangi in assisting victims of trafficking in persons (TTPO) as a response to the serious issue of human exploitation and trafficking in Indonesia. TTPO practices include human rights violations, including physical, sexual, and economic violence. The foundation provides assistance and protection through a mentoring program, aimed at the physical and emotional recovery of victims, as well as social reintegration. Holistic support includes counseling, psychological recovery, skills training, and legal awdvocacy. This research adopts a qualitative method with a literature review and semi-structured interviews, as well as Robert King Merton's theory of anomy, which describes the gap between social goals and the legitimate means of achieving them. This is influenced by social limitations that encourage individuals to achieve goals without legal channels.